THE“SHÈNG NǙ” SOLUTION TO FEMALE MAIN CHARACTER IN THE 《剩者为王》MOVIE’S: FEMINISM ANALYSIS - Pratiwi, Hervita Thalia; Erwani, Intan (Journal of Language, Literature and Teaching, 2023)
ABSTRACTThe title of this research is the“shèng nǚ” label solution to female main character in the 《剩者为王》movie’s: feminism analysis. In this study the background of the rise of female phenomena aged over 27 years but still does not have the desire to get married so that researchers adjust the formulation of the problem how women look for ways to be free from the shackles of which are labeled shèng nǚ to them, especially in the film “shèng zhě wéi wáng”. The purpose of this research is carried out to describe the way the shèng nǚ women are in order to be in accordance with the norms of the community in their own country. In this assessment, researchers use qualitative descriptive methods and data validity through triangulation by using the film